Pengaruh Nano-emulsi Minyak Wijen dan Sereh sebagai Edible Coating terhadap Karakteristik Fisiko-Kimia dan Sensoris Pasca Panen Wortel (Daucus carota L) - Tarigan, Hardiano; Utama, I Made Supartha; Wirawan, I Putu Surya; Janurianti, Ni Made Defy (Jurnal BETA (Biosistem dan Teknik Pertanian), 2025)
Carrot (Daucuscarota L)isa type of vegetablethatduringstorageeasily experiencesquality deterioration which is the cause of high shrinkage. This study aims to determine the effect of sesame and lemongrass oil nanoemulsion concentration as edible coating on the physico-chemical and sensory characteristics of carrots during postharvest. This study used a completely randomised design (CRD) with two factors. The first factor was sesame oil (W) which consisted of three concentration levels, namely: 0%, 0.5% and 1% and the second factor was lemongrass oil (S) which consisted of three concentration levels, namely: 0%, 0.5% and 1%.The study was repeated twice resulting in 18 experimental units. The results showed that in general, sesame and lemongrass oil nano-emulsion significantly affected the weight loss, bulb hardness, collor diference, total soluble solids, vitamin A, and sensory value of carrots during storage. The treatment of 1% sesame oil concentration and 0.5% lemongrass (W2S1) as nano-emulsion on the 15th day of observationwas thebest treatment forweight loss,hardness,totalsoluble solids,and vitamin Acontentof carrot bulbs during20 days of observation.Whilethe concentrationof 1% sesame oiland 0% lemongrass (W2S0),was the best concentration inmaintainingcolourchange andsensory value with a likinglevel of 2.97 on day 15.